2023 HRS/APHRS/LAHRS guideline on cardiac physiologic pacing for the avoidance and mitigation of heart failure - Mina K. Chung; Kristen K. Patton; Chu‐Pak Lau; Alexander Romeno Janner Dal Forno; Sana M. Al‐Khatib; Vanita Arora; Ulrika Birgersdotter‐Green; Yong‐Mei Cha; Eugene H. Chung; Edmond M. Cronin; Anne B. Curtis; Iwona Cygankiewicz; et al. (2023)
Cardiac physiologic pacing (CPP), encompassing cardiac resynchronization therapy (CRT) and conduction system pacing (CSP), has emerged as a pacing therapy strategy that may mitigate or prevent the development of heart failure (HF) in patients with ventricular dyssynchrony or pacing-induced cardiomyopathy. This clinical practice guideline is intended to provide guidance on indications for CRT for HF therapy and CPP in patients with pacemaker indications or HF, patient selection, pre-procedure evaluation and preparation, implant procedure management, follow-up evaluation and optimization of CPP response, and use in pediatric populations. Gaps in knowledge, pointing to new directions for future research, are also identified.